Faktor-Faktor yang Mempengaruhi Kelengkapan Pengungkapan Wajib dalam Laporan Keuangan pada Perusahaan Manufaktur yang terdaftar di BEI - Linda Santioso; Yenny Yenny (The Winners, 2012)
The purpose of this research was to determine the influence of leverage ratio, liquidity ratio, profitability ratio, the portion of stocks owned by public, firm size, and company ages on mandatory disclosure comprehensiveness of financial statement. The sample consisted of 80 manufacturing companies listed at Indonesia Stock Exchange from 2008-2010 selected using purposive sampling method. Descriptive statistics and the multiple regression method were used to analyze the hypotheses. The results of this research showed that only firm size that influence the mandatory disclosure positively and liquidity ratio that influence the mandatory disclosure negatively. This research also showed that there was no autocorrelation, multicollinearity, and heteroscedasticity.